Exploring the factors affecting preschool educators' health teaching capacity of life skills using the PRECEDE model: a study of preschool educators in northern Taiwan - Hui Ling Chen; Wei Hsiang Huang; Chieh Hsing Liu (BMC, 2022)
Abstract Background The purpose of this study was to apply the Predisposing, Reinforcing, and Enabling Constructs in Educational Diagnosis and Evaluation (PRECEDE) model to analyze the factors influencing preschool educators' ability to teach health education through life skills. Methods This cross-sectional study utilized stratified random sampling and administered survey questionnaires to 503 preschool educators in public and private kindergartens in Taipei City and New Taipei City in 2019. Descriptive and hierarchical regression analyses were conducted. The PRECEDE model demonstrated a significant correlation between the enabling, reinforcing, and predisposing factors explored in this study and the preschool educators' ability to teach health education through life skills. Results The variables explained 25% of the total variance in the ability to teach health education through life skills. When controlled in individual layers, the background variables and the enabling, reinforcing, and predisposing factors demonstrated explanatory powers of 6, 5, 7, and 7%, respectively, with respect to the ability to teach health education by utilizing life skills. Conclusions Enhancement of the enabling, reinforcing, and predisposing factors can improve preschool educators' ability to teach health education through life skills. The support provided by the governmental policies for related training can facilitate the effective implementation of health promotion programs in kindergartens. Preschool educators must also receive on-the-job training to facilitate the effective transaction of the health education curriculum. Health classes centered on life skills in kindergartens are vital and must be incorporated into the curricula.